Rate cycles - Kristin Forbes; Jongrim Ha; M. Ayhan Kose (Koç University-TÜSIAD Economic Research Forum (ERF), 2024)
We analyse cycles in policy interest rates in 24 advanced economies over 1970-2024, combining a new application of business cycle methodology with rich time-series decompositions of the shocks driving rate movements. "Rate cycles" have gradually evolved over time, with less frequent cyclical turning points, more moderate tightening phases, and a larger role for global shocks. Against this backdrop, the 2020-24 rate cycle has been unprecedented in many dimensions: it features the fastest pivot from active easing to a tightening phase, followed by the most globally synchronized tightening, and an unusually long period of holding rates constant. It also exhibits the largest role for global shocks- with global demand shocks still dominant, but an increased role for global supply shocks in explaining interest rate movements. Inflation and the growth in output and employment have, on average, largely returned to historical norms for this stage in a tightening phase. Any recalibration of interest rates going forward should be gradual, however, taking into account the interactions between increasingly important global factors and domestic circumstances, combined with uncertainty as to whether rate cycles have reverted to pre-2008 patterns.
Keywords: E52; E31; E32; Q43; 330; Monetary policy; Oil prices; demand shocks; supply shocks; ECB; Federal Reserve